MATING BEHAVIOUR OF CROCIDOLOMIA PAVONANA F. - Purwatiningsih Purwatiningsih; Mirza Devara (UPT Penerbitan Universitas Jember, 2016)
The sequence and duration of mating behaviour Crocidolomia pavonana were observed and investigated by using ethogram time budgets. This research was conducted in the dark hours from 18:00 pm to 06.00 am. The results showed that C. pavonana mating behaviour consists of calling behaviour , courtship behaviour, copulation and oviposition behaviour. Behaviour of copulation was dominated among other behaviour. It took about 48% of on all mating steps behaviour. However, the frequency of the calling leaded by 70.8 times among other behaviour.